Genotype imputation methods for next generation datasets - Rubinacci, S (2020)
The advent of genome-wide association studies (GWAS) revolutionized the field of complex disease genetics. The primary goal of these studies is to achieve a better understanding of the biology of a complex disease and use this knowledge for prevention or better treatment of diseases. Genotype imputation is one of the key steps in such studies. The contribution of genotype imputation is to increase the power of study by boosting the coverage of genetic variation and to provide a natural framework for combining results across association studies that rely on different genotyping platforms.